2012
DOI: 10.4067/s0716-97602012000400007
|View full text |Cite
|
Sign up to set email alerts
|

lnterleukin-8 gene polymorphism and susceptibility to gastric cancer in a brazilian population

Abstract: BACKGROUND: Studies have demonstrated that some polymorphisms in diff erent interleukin genes may increase the risk of cancer. The aim of this study was to investigate the association between the IL-8 (rs4073) -251A/T gene polymorphism and the risk of gastric cancer (GC). PATIENTS AND METHODS: A case-control study was conducted on patients with noncardia gastric cancer. DNA was extracted from leukocytes and the IL-8 (rs4073) -251A/T polymorphism was analyzed by PCR-RFLP. Infection with Helicobacter pylori was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
6
2
Order By: Relevance
“…Among the SNPs of the IL-8 gene evaluated, IL-8-251 A/T is the one that is most commonly related to increased risk for and poor prognosis of several diseases, including gastric cancer [52][53][54]. However, our results did not show increased susceptibility to the gastric diseases evaluated for their ; and e and f IL-10-592 CC (wild-type) and CA+AA (polymorphic).…”
Section: Discussioncontrasting
confidence: 76%
“…Among the SNPs of the IL-8 gene evaluated, IL-8-251 A/T is the one that is most commonly related to increased risk for and poor prognosis of several diseases, including gastric cancer [52][53][54]. However, our results did not show increased susceptibility to the gastric diseases evaluated for their ; and e and f IL-10-592 CC (wild-type) and CA+AA (polymorphic).…”
Section: Discussioncontrasting
confidence: 76%
“…71 Moreover, a Brazilian study found that individuals with A/A genotype may have protective effect for gastric cancer. 72 These contrasting results suggest that IL-8-251T/A SNP may be associated differently with gastric diseases depending on the ethnicity. pylori infection and suggested the occurrence of repeated transmission of H. pylori (same or different strain) between the individuals who live in the same household, due to a greater opportunity of personal contact.…”
Section: 7879contrasting
confidence: 38%
“…Mutations in the CYP1A1 , GSTM1 , MTHFR , SRD5A2 , AR , and GSTA1 genes were relevant in prostate cancer in Latin Americans [108,109,110,111,112], also determined in Caucasians and Asians [113,114,115,116,117,118,119,120,121]. The IL-1 , TP53 , WNT , 8q24 region and IL-8 genes were consistent with gastric cancer in Latin Americans [122,123,124,125,126], as well as in some Asians and Caucasians [127,128,129,130]. The CDKN2A and MC1R genes were related with myeloma in Latin Americans [131], as well as in Caucasians [132,133].…”
Section: Germline Cancer Predisposition In Latin Americamentioning
confidence: 98%